2015
DOI: 10.1007/s00520-015-2924-1
|View full text |Cite
|
Sign up to set email alerts
|

Poor chemotherapy-induced nausea and vomiting control in children receiving intermediate or high dose methotrexate

Abstract: The poor complete CINV control rate in children receiving methotrexate confirms the classification of HD-MTX as highly emetogenic chemotherapy (HEC) and suggests that ID-MTX be reclassified as HEC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…In three studies, 2e4 younger than 50 years was associated with increased risk for CIN, whereas in two studies, 5,6 no age association was found. Similarly, in three studies, 2,3,5 female patients were more likely to report CIN, whereas in three studies, 2,6,7 no association was reported.…”
Section: Introductionmentioning
confidence: 83%
“…In three studies, 2e4 younger than 50 years was associated with increased risk for CIN, whereas in two studies, 5,6 no age association was found. Similarly, in three studies, 2,3,5 female patients were more likely to report CIN, whereas in three studies, 2,6,7 no association was reported.…”
Section: Introductionmentioning
confidence: 83%
“…Nausea has a higher incidence than vomiting during administration of chemotherapy, but it is a challenge to recognize subjective symptoms such as nausea in children. Furthermore, children under 4 years of age are often excluded from studies that investigate the burden of chemotherapy-induced nausea and vomiting in children [ 32 - 34 ]. The target users of this app are children aged 0 to 18 years (and their parents) undergoing cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of CIN in pediatric patients has only recently been possible through the development and validation of pediatric, self‐report measures like the Pediatric Nausea Assessment Tool (PeNAT) . Recent studies indicate that almost all pediatric patients receiving highly emetogenic chemotherapy (HEC) experience CIN …”
Section: Introductionmentioning
confidence: 99%
“…2 Recent studies indicate that almost all pediatric patients receiving highly emetogenic chemotherapy (HEC) experience CIN. 3,4 Many patients and families are interested in using nonpharmacologic therapies to control symptoms. 5 Acupuncture and acupressure are traditional Chinese medicine techniques that seek to improve health by regulating basal energy through acupoint stimulation.…”
Section: Introductionmentioning
confidence: 99%